SLR: Faktor-Faktor yang Mempengaruhi Kepatuhan Protokol Kesehatan COVID-19 - Lindra Anggorowati; Dwi Nur Siti Marchamah; Lukman Fauzi; Wahyu Eko Giri Kusumo (Universitas Ivet, 2023)
Compliance with the Covid-19 health protocol will determine the success of handling COVID-19. In fact it is not easy to build compliance with health protocols in the community in handling COVID-19 in various countries, including Indonesia. Searches related to compliance with health protocols in this study were carried out using the PRISMA method to obtain 8 literature from 1558 articles obtained from Pubmed and Scopus. The analysis shows that adherence to health protocols carried out, both in efforts to wash hands, use masks, not shake hands and avoid crowds, is greatly influenced by the knowledge and motivation a person has.